Determining the degree of cigarette addiction of pregnant smokers - Aydın, Yasemin; Aslan, Ergül (Journal of Dependence, 2015)
Objective: The aim of this study was to determine the level of cigarette addiction of pregnant smokers during the second and third trimesters.Materials and Methods: This descriptive and cross-sectional study, which was carried out at Istanbul Zeynep Kamil Women’s and Children’s Diseases Educational and Research Hospital from January to December 2013, included 165 healthy, volunteer participants in their second and third trimesters of pregnancy.Results: The average age of participants in this study was 27.09±4.93 years. It was observed that, during their pregnancies, 47.3 % of them smoked four or less cigarettes per day and 52.7 % of them smoked five or more cigarettes per day. Of these women, 34% were found to have mild addictions and 46% had severe addictions. As for the women’s husbands, 69.7% of them were smokers, too. A total of 93.9% of the women expressed in our study a belief that smoking was “harmful for the baby”. It became apparent that the pregnant women felt they didn’t have access to advice or support from health care workers in regard to how to stop smoking.Conclusion: Although most of the pregnancies in our study were planned and the expectant mothers knew that smoking was harmful to the baby’s health, they continued to smoke and didn’t consider quitting even following their deliveries. To combat this, effective counseling must be given to pregnant women in antenatal care, including education and support related to smoking cessation methods.
Keywords: Smoking; pregnancy; addiction